ACUTE PHASE OF SYSTEMIC INFLAMMATORY RESPONSE FOLLOWING A SINGLE-PORT LAPAROSCOPIC CHOLECYSTECTOMY - A. V. Alekberzade; E. M. Lypnitskiy; J. A. Badalov (Медицинская иммунология, 2016)
Early course of acute systemic inflammatory response after surgical intervention was traced for sixty-four patients with chronic calculous cholecystitis following a laparoscopic cholecystectomy (LCE). The patients were classified in 2 groups dependent on the surgery mode. The main group included 32 patients after single-port LCE, and controls that underwent four-port LCE (n = 32). Peripheral blood samples were taken 2 h before intervention, as well as 6, 24, and 48 h after surgical treatment. of Alpha-1-antitrypsin (A1AT), C-reactive protein, TNFα and IL-1β levels were measured in the specimens. For A1AT, we have not found any significant differences between the baseline and post-surgery levels, both in main and control groups. The intergroup comparisons showed a statistically significant increase in A1AT levels 24 h after the 4-port LCE. The patients subjected to single-port LCE, exhibited similar pre- and post-surgery levels of C-reactive protein. In the control group, its level proved to be statistically higher against initial values 6 h after the surgery. Comparing the both groups, C-reactive protein was found to be significantly increased in controls 6 и 24 h after surgery.The post-op TNFα levels after the single-port LCE tended to increase, as compared to the baseline values. A statistical increase of TNF levels over initial values was noted 24 h after the 4-port LCE. Upon the intergroup comparisons, a significant TNF increase was revealed 24 following the 4-port LCE. IL-1β levels in the main group did not differ between the pre- and post-surgical period. However, its statistically significant increase to the initial values was revealed in controls 24 h after surgery. A comparison for IL-1β levels between the 2 groups has shown its significant elevation 24 h after the 4-port LCE. These data allow to conclude that a systemic inflammatory response as assessed by acute phase proteins in patients after a single-port LCE, is characterized by a shorter and less marked inflammatory reaction, as compared to the reaction in patients after the 4-port LCE.